2022
DOI: 10.1186/s13059-022-02801-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive transcriptional variability analysis reveals gene networks regulating seed oil content of Brassica napus

Abstract: Background Regulation of gene expression plays an essential role in controlling the phenotypes of plants. Brassica napus (B. napus) is an important source for the vegetable oil in the world, and the seed oil content is an important trait of B. napus. Results We perform a comprehensive analysis of the transcriptional variability in the seeds of B. napus at two developmental stages, 20 and 40 days after flowering (DAF). We detect 53,759 and 53,550 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…However, the asymmetry between subgenomes also opens some interesting questions about their individual contributions to trait regulation. For example, in a recent report, more SNP-eQTLs were identified on the A subgenome compared to the C-subgenome (Tan et al 2022). Our results agree with this finding.…”
Section: Resultsmentioning
confidence: 99%
“…However, the asymmetry between subgenomes also opens some interesting questions about their individual contributions to trait regulation. For example, in a recent report, more SNP-eQTLs were identified on the A subgenome compared to the C-subgenome (Tan et al 2022). Our results agree with this finding.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with mGWAS, mTWAS tend to use the expression level of a certain gene, eliminating the uncertainty of linkage disequilibrium interval and screening candidate genes more accurately and directly [ 68 , 69 ]. Our previous study comprehensively characterized the transcriptional variability in developing seeds of B. napus and successfully cloned two transcription factors involved in the regulation of SOC from eQTL hotspots87-88 [ 70 ]. The metabolome variation data has brought more information which helped predict novel genes regulating SOC by marker metabolite-based multi-omics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…SCARECROW‐LIKE 31 ( BnA09.SCL31 ) and NAC DOMAIN CONTAINING PROTEIN 13 ( BnNAC13s ) were predicted to be the key transcription factors affecting SOC. Overexpression of two homologous copies of BnNAC13s in Arabidopsis was found to significantly alter SOC (Tan et al, 2022a). Further, in combination with metabolomic data, two key genes affecting SOC, TRANSPARENT TESTA 4 ( BnTT4 ) and BnC05.UK were successfully cloned (Li et al, 2023b).…”
Section: Seed Qualitymentioning
confidence: 99%
“…The large numbers of homologous gene copies lead to gene redundancy and dose effects, making it more difficult to verify gene function. Previous studies have also found imbalances between subgenomes in terms of gene expression, epigenetic activity, and single nucleotide polymorphism variations (Zhou et al, 2017; Zhang et al, 2021; Tan et al, 2022a), which present challenges for deciphering the gene regulatory network in B. napus . Possible reasons for this imbalance include increased heterozygosity between B. napus and B. rapa , as well as limited Cn genomic diversity resulting from primary allopolyploid (Li et al, 2006).…”
Section: Challeges and Perspectivesmentioning
confidence: 99%